The Role of Teachers in Child-Friendly School Programs di SDIT An-Nur Kab. Muara Jambi - Rahmi Putri; Ambiyar Ambiyar; Ishak Azis (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
Child-friendly schools, or SRA for short, are schools that prioritize the safety, welfare, and rights of their students and take steps to ensure that they are free from threats of violence and discrimination. The purpose of this study is to Describe the Planning, Implementation, and Monitoring Implementation of the Child-Friendly School Program at SDIT An-Nur, Muara Jambi Regency. A qualitative research method with a descriptive approach is used in this study. The results of the study showed: 1) The planning that was completed at SDIT An-Nur, Muaro Jambi Regency, succeeded in meeting the standard requirements for SRA program planning. 2) The implementation of a Child-Friendly School at SDIT An-Nur, Muara Jambi Regency, was very successful and met the SRA indicators and received an award from the City Education Office at the Green School Festival activity with the nomination of the best SD-S at the Child-Friendly School level in Jambi City. 3) For monitoring, the researcher sent a pre-made questionnaire to representatives of the principal and teaching staff at SDIT An-Nur in Muara Jambi Regency and asked them to fill it out. Then the questionnaire was reviewed by the relevant agencies and services. The evaluation of the SRA program at SDIT An-Nur, Muara Jambi Regency, was compared and contrasted with the overall program evaluation.